Cigarette smoke represses the innate immune response to asbestos. Issue 12 (10th December 2015) - Morris, Gilbert F.; Danchuk, Svitlana; Wang, Yu; Xu, Beibei; Rando, Roy J.; Brody, Arnold R.; Shan, Bin; Sullivan, Deborah E.
Abstract: Both cigarette smoke (CS) and asbestos cause lung inflammation and lung cancer, and at high asbestos exposure levels, populations exposed to both of these carcinogens display a synergistic increase in the development of lung cancer. The mechanisms through which these two toxic agents interact to promote lung tumorigenesis are poorly understood. Here, we begin to dissect the inflammatory signals induced by asbestos in combination with CS using a rodent inhalation model and in vitro cell culture. Wild‐type C57BL/6 mice were exposed to room air as a control, CS, and/or asbestos (4 days per week to CS and 1 day per week to asbestos for 5 weeks). Bronchoalveolar lavage (BAL) fluid was collected following exposure and analyzed for inflammatory mediators. Asbestos‐exposed mice displayed an increased innate immune response consistent with NLRP3 inflammasome activation. Compared to mice exposed only to asbestos, animals coexposed to CS + asbestos displayed attenuated levels of innate immune mediators and altered inflammatory cell recruitment. Histopathological changes in CS + asbestos‐exposed mice correlated with attenuated fibroproliferative lesion development relative to their counterparts exposed only to asbestos. In vitro experiments using a human monocyte cell line (THP‐1 cells) supported the in vivo results in that coexposure to cigarette smoke extract repressed NLRP3 inflammasome markers in cells treated with asbestos. These observations indicate that CS represses central components of the innate immune response to inhaled asbestos. Abstract : Subchronic exposure to cigarette smoke represses activation of the innate immune response to inhaled asbestos in a mouse model. The finding that cigarette smoke represses the innate immune response to asbestos adds to a growing body of literature that cigarette smoke impairs immune surveillance in the lung.